2017
DOI: 10.1002/cncr.30783
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among Holocaust survivors in Israel—A nationwide study

Abstract: The current results, based on a large cohort of Holocaust survivors who were exposed to a variety of severe deprivations, add to the conflicting and sparse knowledge on this issue and support the notion that this group has a small but consistent increase in cancer development. Cancer 2017;123:3335-45. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
(107 reference statements)
2
30
0
Order By: Relevance
“…We read with interest the article by Sadetzki et al, 1 which confirmed our own findings regarding the increased cancer risk in Israeli Holocaust survivors. 2 The higher risk for cancer of all sites as well colorectal and lung cancer in exposed subjects observed in both studies despite the different methodologies used further validates these results.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…We read with interest the article by Sadetzki et al, 1 which confirmed our own findings regarding the increased cancer risk in Israeli Holocaust survivors. 2 The higher risk for cancer of all sites as well colorectal and lung cancer in exposed subjects observed in both studies despite the different methodologies used further validates these results.…”
supporting
confidence: 84%
“…This can be seen in Table 1 in our study, 1 which shows that approximately 29% of the study population immigrated after 1960, and that many of these individuals were classified as exposed (particularly in the group B and disabled war veterans subgroups). 1 The second point raised in the letter by Keinan Boker and Vin-Raviv is that our study population did not include all Holocaust survivors who immigrated to Israel. Not only do we agree that our study population cohort included Holocaust survivors who applied for compensation as per Israeli laws, we also have mentioned that only approximately 40% of the Jews who survived World War II were living in Israel, thereby raising the question of the generalization of the findings.…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Sadetzki et al, reported in this issue 1 , showcases the impact of a horrendous event – the Holocaust – on subsequent health, decades after the occurrence. This study not only brings to light additional effects of the Holocaust in the Jewish population, but brings to mind similarities in cancer development and extreme population-level tragedies.…”
mentioning
confidence: 98%
“…In the article by Sadetzki et al in this issue, exposure to the horrific stressors of the Holocaust is associated with an increased risk of subsequent cancers, although there was not an association with breast cancer. 1 The stressors of Holocaust survivors went far beyond those of victims of the Norway food restrictions and those who suffered from the Dutch famine. Stressors were emotional and physical, and the duration of the abuses was both long and continuous.…”
mentioning
confidence: 99%